Spiritual anatomy and vernacular spatial autonomy - the case of Ghantasala village, Andhra Pradesh - Venkata Krishna Kumar Sadhu; Amitava Sarkar Ramesh Srikonda
Spirituality is about being conscious of the vital force or breath (prana) which is considered essential in traditional Indian thought. It is said that a joyful heart attracts grace. Since ancient times, there has been a long-standing connection between spirituality and building. Many societies have thought of architecture as a way to represent their spiritual practices and beliefs throughout history. In this way, architecture establishes a symbolic space for introspection and cultural expression. Hence, the study has been conducted in Ghantasala village of Krishna district, Andhra Pradesh. The village is considered to be one of the settlements having vernacular houses of more than hundred years of age. The aim of the study is to assess the relation between vernacular architecture and spirituality. This paper attempts to appreciate spiritual anatomy and spatial autonomy in parallel wherever relevant. For the same, qualitative research methodology has been deployed consisting of comparison of the quality of spaces in a vernacular house vis-a-vis a non-vernacular house, through a physical, questionnaire$1 (Band perception survey of the users of vernacular houses. Quantitative analysis is also done through statistical analysis, to assess happiness of the users of a vernacular house in comparison with the happiness of the same users in case of a non-vernacular house. It was found that the journey of vernacular architecture from design to execution represents an evolution of the user$1 (Bs happiness and wellbeing from thinking to feeling to being to becoming. Findings of the study further show that the users of a vernacular house expressed acceptance of and happiness with a vernacular house than a non-vernacular house. However, the users of vernacular houses expressed certain compelling reasons for transforming the vernacular houses to non-vernacular houses owing to issues related to cost, availability of workers skilled in vernacular methods, etc. There is a scope for further research to check relevance of the same for settlements of this kind in other geographical areas of India and assess the level of replicability.s